Three dimensional user interface for Islamic heritage education and exhibition applications - a proposal - Abu Bakar, Juliana Aida; Jahn Kassim, Puteri Shireen (2008)
The field of virtual cultural heritage refers to the use of virtual reality systems to generate, navigate and explore reconstructed environments that are of cultural interest. This emerges from the term digital heritage that refers to the use of digital technology especially computer systems to preserve and communicate cultural heritage. The use of three-dimension (3D) user interfaces CUI) such as textured 3D model, virtual environment (VE), augmented reality (AR), or mixed reality (MR) is increasing in virtual cultural heritage projects. These interfaces allow different aspects of the 3D model to be explored and accessed extensively for accurate interpretation. This paper proposes a 3D user interface virtual cultural heritage focusing on effective learning to Islamic heritage studies. It describes previous work in the area and further outlines the research directions.